Work Environment, Auditor Fees, and Culture on Future Accounting Careers: Lingkungan Kerja, Biaya Auditor, dan Budaya Terhadap Masa Depan Karir Akuntansi - Restu, Firda Dini; abidin, Fityan izza noor (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: As the demand for qualified auditors continues to rise, it is essential to investigate how various determinants affect future career decisions in this field. Specific Background: Prior research has highlighted the significance of the audit work environment and auditor fees, yet the role of socio-cultural factors remains underexplored. Knowledge Gap: This study addresses this gap by examining the impact of the audit work environment, auditor fees, and socio-cultural factors on the career aspirations of accounting students at Universitas Muhammadiyah Sidoarjo. Aims: Utilizing a quantitative approach, the research aims to analyze the relationships among these variables and their influence on future career choices. Results: Data were collected from 156 respondents via a structured questionnaire, analyzed using multiple linear regression. Findings indicate a positive correlation between the audit work environment and auditor fees on students' career choices, while socio-cultural factors also significantly impact their decisions. Novelty: This study contributes to the existing literature by integrating socio-cultural dimensions into the analysis of career choice determinants for accounting students, highlighting the multifaceted nature of career decision-making. Implications: The study emphasizes the need for educational institutions and policymakers to consider these factors when creating career guidance programs for students in the accounting sector. Highlights: Impact Assessment: Examines how audit environment and fees affect career choices. Socio-Cultural Relevance: Highlights socio-cultural factors' influence on accounting career decisions. Educational Implications: Calls for tailored guidance in accounting education programs. Keywords: accounting career choices, audit work environment, auditor fees, socio-cultural factors, quantitative research